Characteristics of candidemia in COVID‐19 patients; increased incidence, earlier occurrence and higher mortality rates compared to non‐COVID‐19 patients. Issue 9 (16th June 2021) - Kayaaslan, Bircan; Eser, Fatma; Kaya Kalem, Ayşe; Bilgic, Zeynep; Asilturk, Dilek; Hasanoglu, Imran; Ayhan, Muge; Tezer Tekce, Yasemin; Erdem, Deniz; Turan, Sema; Mumcuoglu, Ipek; Guner, Rahmet
Abstract: Severe COVID‐19 patients in ICU are at high risk for candidemia due to exposure to multiple risk factors for candidemia. We aimed to compare the incidence of candidemia in ICU patients with and without COVID‐19, and to investigate epidemiologic and clinical characteristics of candidemia patients and risk factors for mortality in candidemia patients. This retrospective study was conducted in patients followed in the ICUs of Ankara City Hospital for 2 years, divided into pre‐pandemic and pandemic periods. The incidence (event per 1000 patient‐days) and epidemiology of candidemia, clinical and laboratory characteristics of patients were compared in COVID‐19 and non‐COVID‐19 groups. Candidemia incidence was higher in the COVID‐19 group (2.16, 95% CI 1.77–2.60) than the non‐COVID‐19 group (1.06, 95% CI 0.89–0.125) ( p  < .001). A total of 236 candidemia episodes (105 in COVID‐19 patients and 131 in non‐COVID‐19 patients) were detected during the study periods. COVID‐19 cases had a higher rate of corticosteroid use (63.8% vs. 9.9%, p  < .001). Epidemiology of candidemia and antifungal susceptibility were similar. Candidemia developed 2 weeks earlier in COVID‐19 groups and resulted in higher mortality (92.5% vs. 79.4%, p .005). One‐third of candidemia patients died before receiving any antifungal treatment, and this rate was higher in the COVID‐19 group. In multivariate logistic regression analysis, corticosteroid use, presence of sepsis and age older than 65 years were independent risk factors for mortality in candidemia patients. Candidemia with high mortality is a more serious problem for COVID‐19 patients due to its increased incidence, earlier occurrence and a higher rate of mortality.